Descemet’s membrane endothelial keratoplasty for acute corneal hydrops: a case report - Maranhão,Lucio V. L (2020)
ABSTRACT Here, we describe the result of a Descemet’s membrane endothelial keratoplasty for acute corneal hydrops in a 45-year-old female with keratoconus, who presented with severe visual loss in her OS. The patient’s best-corrected visual acuity was 20/80 in the right eye and hand motion in the OS. Slit-lamp examination revealed an extensive tear of the Descemet’s membrane and stromal corneal edema in the OS. We opted for Descemet membrane endothelial keratoplasty. Twelve months postoperatively, the patient had a best-corrected visual acuity of 20/50 in the OS.